Preparation of the Eu-Co-Ni-B coating from anhydrous ethanol at low temperature and effects of heat treatment on the coating. Issue 6 (2nd May 2022) - Zhang, Shimin; Gao, Lixia; Xiong, Tongtong; Chen, Biqing; Du, Chan; Zhu, Yunna; Zhao, Jing
Abstract: In this paper, the Eu-Co-Ni-B coating was successfully prepared on the surface of copper from anhydrous ethanol at low temperature (40 °C) by electroless plating. The surface morphology of the coating was observed using Scanning Electron Microscopy (SEM), the composition was analyzed by Energy Dispersive X-Ray Spectroscopy (EDX), while the structure was studied by the X-ray Diffraction (XRD). In order to investigate the effects of heat treatment on the Eu-Co-Ni-B coating, the coating was heat treated at 200 °C, 400 °C, 600 °C and 800 °C for 40 min. The results showed that the Eu-Co-Ni-B coating changed from amorphous to crystalline. Open circuit potential (OCP) measurements and potentiodynamic polarization (PDP) experiments were carried out in 3 wt. % NaCl and 1 M NaOH to determine the anticorrosion performance of the coating. The 400 °C annealed coating showed notable improvement in corrosion properties. Graphical Abstract: UF0001